EVALUASI SIFAT FISIKOKIMIA TEMPE WARNA DENGAN PENGGUNAAN KUNYIT SEBAGAI PEWARNA ALAMI DAN PENAMBAHAN SDB ( Sabouraud Dextrose Broth) - Sihmawati, Rini Rahayu; Panjaitan, Tiurma W. Susanti; Rosida, Dwi Agustiyah (Heuristic, 2017)
This research is determining the impact of adding natural dyes turmeric and Sabouraud Dextrose Broth (SDB) against physicochemical of tempeh. Benefits of the research is to support the food security program through increased value-added tempeh using natural dyes. This research was conducted by the method of experimental design was completely randomized. The first treatment is concentration of turmeric (K) and the second is the concentration of SDB. The first consists of three concentration levels (0.5% , 1% and 1.5%), and the second also consists of three concentration levels (1% , 2% and 3% ) and repeated 3 times. The test results chemically the protein , fat and ash contents between the tenth treatment showed not significant (P> 0.05), the test results of water content between the ten treatments of at least two show difference (P <0.05), also carbohydrate (P <0:01).Keywords: physicochemical, colored tempeh, turmeric, natural dyes, SDB